School Water, Sanitation, and Hygiene: A Systematic Review of an Effect on Health, Attendance, Regularity, and Educational Achievements (Scholars' Journal, 2022)
The review was started aiming to assess the effect of school-based Water, Sanitation, and Hygiene (WASH) facilities on students’ health status, school regularity, and educational achievement. Two major academic and scientific research journals as Springer and PubMed have been selected, where WASH is the search engines, separately. There were 8,443 relevant publications found, with Springer having6, 888 and PubMed having 1,555. Among these publications, author synthesized 17 with abstracts and full articles, including references for this study. The findings of this study indicates that intervention of school WASH facilities have an effect on students’ health status, regularity in school attendance, and educational achievement. It protects students from various infectious diseases caused by poor WASH access; however, ways of handling it is equally important. The intervention in WASH facilities at school improves students’ health, school regularity, and educational achievements. Thus, the study strongly suggests interventions in school-based WASH facilities to make students healthier, more regular, and better academic performer.